The (De)Legitimisation of Lithuanian Opposition to Ostrovets Nuclear Power Plant Through International Atomic Energy Agency - Juozaitis, Justinas (Politologija, 2020)
Lithuanian foreign policy perceives International Atomic Energy Agency (IAEA) as an organization with the most significant authority in nuclear safety, capable of assessing Ostrovets NPP’s compliance with international nuclear safety standards objectively. Simultaneously, the IAEA is one of the most important international institutions through which Lithuania sought to reveal the shortcomings of the Ostrovets NPP while attempting to legitimize its critical position towards the power plant. Given the relevance of IAEA in Lithuanian foreign policy, the article examines IAEA’s public discourse on nuclear energy in Belarus. It aims to assess its role in the process of legitimizing Lithuania’s opposition to Ostrovets NPP. After analyzing the IAEA’s leadership statements, the official press releases and the reports published by the peer-review missions during 2007 – 2020, the paper concludes that the IAEA formed a public discourse that exclusively favoured Belarus and significantly contradicted to Lithuania’s official position. In this way, the IAEA did not legitimize Lithuania’s foreign policy towards Ostrovets NPP. On the contrary, the organization supported nuclear energy development in Belarus. In relation with the findings, the paper provides three suggestions for reshaping the role of IAEA in Lithuanian foreign policy.